Proliferating Pilar Tumors: Could Immunohistochemistry be Helpful to Differ Benign and Malignant Forms? - Yildiz, Pelin; Ulgen, Ovgu Aydin; Yol, Cansu; Demirkesen, Cuyan (NATURE PUBLISHING GROUP, 2020)
109th Annual Meeting of the United-States-and-Canadian-Academy-of-Pathology (USCAP), Los Angeles, CA, FEB 29-MAR 05, 2020